THE EFFECT OF ONLINE TAX SERVICES ON TAX COMPLIANCE - Deda Ayu Alipia (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2022)
The purpose of this study was to determine and analyse the effect of the application of online tax services on taxpayer compliance in Subang Regency. The data in this study were obtained from questionnaires as primary data distributed to taxpayers registered at KPP Pratama Subang. The population of this study were individual taxpayers registered as taxpayers at the Subang Primary Tax Office. The number of samples used in this study were 30 respondents. The data collection technique in this study used purposive sampling technique. The analysis technique uses linear regression analysis with a significance level of 5%. The results of this study indicate that the application of online tax services has an influence on taxpayer compliance in Subang Regency.